An Investigation of EFL Novice Teachers Causes of Teaching Anxiety and their Coping Strategies - Irhamna, Vidia; Fithriani, Rahmah (Anglophile Journal, 2023)
Anxiety in language teaching and learning is not a new issue. However, there is little information about the anxiety faced by English as a foreign language (EFL) novice teacher, especially in Indonesian context. This study aims to find out the causes of anxiety in teaching English, strategies to overcome this anxiety, and school support in helping teachers manage their anxiety. This qualitative study used an online closed-ended questionnaires and interviews for data collection. Sixteen EFL novice teachers from seven junior high schools and nine senior high schools in Medan, Indonesia participated in this study. The findings reveal three causes of teaching anxiety experienced by the novice teachers, namely: student participation and class situation; material mastery; and lack of confidence. To overcome their anxiety, the teachers used some strategies which include better teaching preparation, establishing communication with students, doing warm up and ice breaking, and creating study groups. In relation to these findings, school support such as provision of teaching/learning resources and facilities, discretion to teachers, and teaching training could aid novice teachers manage their anxiety. Keywords: EFL Novice Teachers, Coping Strategies, Teaching Anxiety